The impact of foreign-owned enterprises in low-income economies. Issue 7 (3rd October 2018) - Lundy, Brandon D.; Patterson, Mark; O'Neill, Alex
ABSTRACT: An economic impact snapshot of foreign and domestic enterprises from the functional economic areas of Guinea-Bissau showed that not all micro and small enterprises (MSEs) are local, and not all outside investment is large scale. We find that South–South entrepreneurship has prospects to improve livelihoods as drivers of economic growth and development in a low-income economy. While political instability and a lack of resources remain as barriers to solvency for both domestic and foreign investors in the global periphery, as opportunities and effective business strategies are fostered, improved socio-economic integration and development results.